Structure soil structure interaction of conventional and base-isolated building subjected to real earthquake. (August 2021) - Bandyopadhyay, Srijit; Parulekar, Y.M.; Sengupta, Aniruddha; Chattopadhyay, J.
Abstract: In this paper, the effect of structure soil structure interaction of the two adjacent Reinforced Concrete (RC) three storied structures, located in highest seismic zone of India are studied. One of the buildings is mounted on base isolator (Lead Rubber Bearing) and the other building is a normal conventional RC framed structure. The buildings were instrumented and real earthquake response of the buildings was captured during the period 2006 to 2007. The frequency of the base isolated structure was lesser than the conventional structure by a factor of 2.6 and the response was also reduced by factor of 4 to 5 as envisaged. However, structure soil structure interaction was observed in the response of the base isolated building and the measured response showed the frequency of the nearby structure. A numerical simulation considering two adjacent structures together with detailed soil modelling is performed and the numerical results are validated with recorded real earthquake data. Furthermore, response of both the buildings are studied with the larger earthquake in the same area with a PGA of 0.26 g and the response acceleration of the base isolated building is reduced by about 4.1 times the conventional building response. Moreover, the floor spectra of the roof of base isolated structure has multiple peaks due to nonlinear deformation of the isolator which gives different effective stiffness for different displacements in the hysteretic deformation of the isolator experienced during cyclic motion. It is also observed that that frequency of the base isolated building reduces with increasing peak ground acceleration.